2020
DOI: 10.1007/s00540-020-02796-6
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia and protection in an emergency cesarean section for pregnant woman infected with a novel coronavirus: case report and literature review

Abstract: An outbreak of novel coronavirus pneumonia occurred worldwide since December 2019, which had been named COVID-19 subsequently. It is extremely transmissive that infection in pregnant women were unavoidable. The delivery process will produce large amount of contaminated media, leaving a challenge for medical personnel to ensure both the safety of the mother and infant and good self-protection. Only rare cases of pregnant women with COVID-19 are available for reference. Here, we report a 30-year-old woman had re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 15 publications
1
33
0
Order By: Relevance
“…55 Although this was not analysed directly with respect to postoperative outcomes, we found that nine of the studies reported conducting surgical procedures in negative pressure operating rooms. 19,21,22,24,28,29,35,36,38 Negative pressure rooms are commonly used in infection control and ensure that air continually flows into the room, rather than the surrounding area. However, most hospitals only have a limited number of negative pressure operating rooms and therefore have to adapt additional rooms for this purpose.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…55 Although this was not analysed directly with respect to postoperative outcomes, we found that nine of the studies reported conducting surgical procedures in negative pressure operating rooms. 19,21,22,24,28,29,35,36,38 Negative pressure rooms are commonly used in infection control and ensure that air continually flows into the room, rather than the surrounding area. However, most hospitals only have a limited number of negative pressure operating rooms and therefore have to adapt additional rooms for this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…Patient use of PPE was poorly reported, with only nine studies stating that patients wore any protection. 19,21e23,28,29,35,38,39 Six of these reported the use of surgical masks only, 19,21,22,28,35,38 with N95 mask respirators specifically mentioned in three studies. 21,22,28 HCW use of PPE was more comprehensively reported, with 16 studies describing perioperative use.…”
Section: Use Of Ppe and Infection Reduction Strategiesmentioning
confidence: 99%
See 3 more Smart Citations